2012
DOI: 10.1016/j.emj.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Work–life balance: One size fits all? An exploratory analysis of the differential effects of career stage

Abstract: Summary This paper explores the antecedents of work-life balance for employees as they progress through different career stages denoted by age. To date, research has failed to adequately explore how work-life balance issues develop over the course of an employeeÕs working life. As a consequence, much of the work-life balance policy and practice research examines WLB issues from a relatively static and unchanging perspective resulting in praxis which is undifferentiated. Such a Ôone size fits allÕ approach to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 50 publications
5
94
1
8
Order By: Relevance
“…Moreover, this paper examined WLB in the context of satisfaction with work and family situations (Grzywacz & Carlson, 2007;Lyness & Judiesch, 2008), but most employees viewed WLB as: enjoyment, effectiveness (Greenhaus & Allen, 2011), stability (Crooker et al, 2002), time (Parasuraman & Greenhaus, 1999) and subjectivity (Darcy et al, 2012;Goodman, 2012). Other employees wished they could reclaim balance, while others indicated their intention to leave the organization and suggested that only then could balance be achieved.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Moreover, this paper examined WLB in the context of satisfaction with work and family situations (Grzywacz & Carlson, 2007;Lyness & Judiesch, 2008), but most employees viewed WLB as: enjoyment, effectiveness (Greenhaus & Allen, 2011), stability (Crooker et al, 2002), time (Parasuraman & Greenhaus, 1999) and subjectivity (Darcy et al, 2012;Goodman, 2012). Other employees wished they could reclaim balance, while others indicated their intention to leave the organization and suggested that only then could balance be achieved.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Work-life balance is achieved when employees experience being engaged and satisfied in caring out the manifold functions with which they recognize them self. Work-life balance is an initiative that assists employees to bring a sense of balance and experiencing accomplishment and fulfilment in work and persons' individual domains (Darcy et al, 2012). Quality of life and work-life balance are found to be highly correlated when participants balance their time in family than work (Greenhaus et al, 2003).…”
Section: Psychological Well Being and Organisational Commitment: Modementioning
confidence: 99%
“…Further, literature suggests that a struggle to achieve work life balance is being experienced by employees in all types of professions worldwide (Darcy et al, 2012). It seems to be difficult to bring balance between job, family and personal life for the employees who devote longer hours at the work place (Hochschild, 1997).…”
Section: Psychological Well Being and Organisational Commitment: Modementioning
confidence: 99%
“…Employees who enjoy their jobs will continue to be attracted to continuing to work in a company which implies a greater commitment to the organization. Therefore, this research will seek to test the following research hypothesis: H2: Workers' welfare has positive effects on their commitment to the company Commitment comes as an acceptance of the employee's goals and values of the company and the willingness to continue as a member of the organization, stresses that work-life balance improvement programs try to raise commitment to the organization [11], [20]. Thus, this study will try to evaluate the following research hypothesis: H3: The balance between work and personal life has positive effects on the commitment of the worker to the companies The companies intend to be the best in their business, however, the ambitions must be realistic according to the resources of the company, so the need to reach the optimum must be realized incrementally.…”
Section: Literature Reviewmentioning
confidence: 99%